Small gold nanoparticles for interfacial Staudinger–Bertozzi ligation1. Issue 15 (21st April 2015) - Gobbo, Pierangelo; Luo, Wilson; Cho, Sung Ju; Wang, Xiaoxiao; Biesinger, Mark C.; Hudson, Robert H. E.; Workentin, Mark S.
<x xml:space="preserve">Abstract</x> Small gold nanoparticles (AuNPs) that possess interfacial methyl-2-(diphenylphosphino)benzoate moieties have been successfully synthesized (Staudinger-AuNPs), characterized and their interfacial reactivity was investigated.